Pengaruh Industri Fast Fashion Terhadap Pencemaran Lingkungan dan Penurunan Keadilan Antar Generasi - Albab, Wildan Ulul; Mardiah, Adinda Rabiki; Ranjani, Gita; Karina, Gladys Donna; Safitri, Masna Nuros (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2024)
The fast fashion industry has grown rapidly over the last few decades and has had a significant impact on environmental degradation. This research aims to determine the impact of the fast fashion industry and how to deal with it. This research was carried out through a normative juridical literature study with a conceptual approach to the various legal literature materials used. Based on the research results, it is known that the impact of the accumulation of waste generated from the fast fashion industry greatly influences the decline in the quality of the environment caused by water pollution, waste disposal and excessive exploitation of natural resources so that it is contrary to the principle of intergenerational justice which emphasizes the importance of protecting natural resources for the benefit of future generations. Efforts to overcome the fast fashion industry waste problem are being carried out by improving regulations in Indonesia regarding the management of fast fashion industry waste which are considered inadequate. The government needs to reform policies regarding fast fashion industry waste management, invest in recycling infrastructure, and change people's consumption patterns to achieve a sustainable fashion industry